Mathematics applied to engineering and management - Ram, Mangey; Singh, S. B. (Engineer) (Boca Raton, FL : CRC Press, imprint of the Taylor & Francis Group, 2020)
This book offers the latest research advances in the field of mathematics applications in engineering sciences and provides a reference with a theoretical and sound background, along with case studies. In recent years, mathematics has had an amazing growth in engineering sciences. It forms the common foundation of all engineering disciplines. This new book provides a comprehensive range of mathematics applied to various fields of engineering for different tasks in fields such as civil engineering, structural engineering, computer science, electrical engineering, among others. It offers articles that develop the applications of mathematics in engineering sciences, conveys the innovative research ideas, offers real-world utility of mathematics, and plays a significant role in the life of academics, practitioners, researchers, and industry leaders. Focuses on the latest research in the field of engineering applications Includes recent findings from various institutions Identifies the gaps in the knowledge of the field and provides the latest approaches Presents international studies and findings in modelling and simulation Offers various mathematical tools, techniques, strategies, and methods across different engineering fields
6: Application of Transmuted Gumbel Copula for Energy Modeling7: Differential Quadrature Method: A Robust Technique to Solve Differential Equations; 8: The TSCSTFCF Procedure for Reliability Demonstration; 9: Reliability Evaluation of a MANET Incorporating Copula; 10: Hydromagnetic Flow of Copper-Water Nanofluid with Different Nanoparticle Shapes toward a Nonlinear Stretchable Plate; 11: Reliability and Sensitivity Assessment of a Sugar Mill through Mathematical Modeling; Index
OCLC-licensed vendor bibliographic record.
Keywords: Engineering mathematics; Industrial management -- Mathematics; MATHEMATICS / Applied; MATHEMATICS / Functional Analysis; TECHNOLOGY / Electricity